24.2k views
0 votes
Use the functions f(x) = x^2 -3 and g(x)= 2x- 1. What is (f.g)(x)

Use the functions f(x) = x^2 -3 and g(x)= 2x- 1. What is (f.g)(x)-example-1
User Karmafunk
by
4.6k points

1 Answer

7 votes

Answer:

2x^3 - x^2 - 6x + 3

Explanation:

(f•g)(x) means

f(x) • g(x)

(But for sure, for real, its multiplication ONLY IF that dot is a multiplication dot. If that dot is an open dot in the original problem, then it is a WHOLE DIFFERENT problem, called function composition)

Continuing on with the multiplication.

f(x) • g(x) =

(x^2 - 3)(2x - 1) =

2x^3 - x^2 - 6x + 1

User Kcsurapaneni
by
4.8k points